2014
DOI: 10.1007/s11302-014-9412-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of adenosine A3 receptors causes defects in mouse peripheral blood parameters

Abstract: The role of the adenosine A 3 receptor in hematopoiesis was studied using adenosine A 3 receptor knockout (A 3 AR KO) mice. Hematological parameters of peripheral blood and femoral bone marrow of irradiated and untreated A 3 AR KO mice and their wild-type (WT) counterparts were investigated. Irradiation of the mice served as a defined hematopoiesis-damaging means enabling us to evaluate contingent differences in the pattern of experimentally induced hematopoietic suppression between the A 3 AR KO mice and WT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…Whether these particular findings reflect also in an aggravation of the parameters like oxygen transport capacity, arterial pO 2 , or platelet aggregation test, an additional experimentation is, however, needed. An also previously described (Hofer et al 2014a) obvious increase in the numbers of the bone marrow hematopoietic progenitor cells, GM-CFC and BFU-E, in the A 3 AR KO mice, explainable as an attempt of the hematopoietic system of these mice to compensate for the peripheral blood cell insufficiency, was observed in this study (see Table 4). In the erythroid compartment, the probable compensatory activity in the A 3 AR KO mice was apparently successful, as follows from their significantly higher blood erythrocyte count and blood hemoglobin level (see Table 2).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Whether these particular findings reflect also in an aggravation of the parameters like oxygen transport capacity, arterial pO 2 , or platelet aggregation test, an additional experimentation is, however, needed. An also previously described (Hofer et al 2014a) obvious increase in the numbers of the bone marrow hematopoietic progenitor cells, GM-CFC and BFU-E, in the A 3 AR KO mice, explainable as an attempt of the hematopoietic system of these mice to compensate for the peripheral blood cell insufficiency, was observed in this study (see Table 4). In the erythroid compartment, the probable compensatory activity in the A 3 AR KO mice was apparently successful, as follows from their significantly higher blood erythrocyte count and blood hemoglobin level (see Table 2).…”
Section: Discussionsupporting
confidence: 84%
“…Thus, defects have been described in the populations of the mouse peripheral blood erythrocytes and platelets of the A 3 AR KO mice (Hofer et al 2013a). The succeeding studies comprising also exposition of A 3 AR KO mice to ionizing radiation have revealed that the defects at the level of mature peripheral blood cells are attempted to be compensated from the level of the bone marrow progenitor cells (Hofer et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Neurotransmission, secretion, transduction, cell proliferation, motility, and differentiation are typical examples of biological functions modulated by nucleotides or nucleosides acting as extracellular signaling molecules [5][6][7][8][9][10][11]. Burnstock's early hypothesis that ATP, the major intracellular molecule providing the energy required for multiple biochemical and biophysical processes, may actually function as an extracellular non-adrenergic and noncholinergic signaling molecule [12,13] was received with great skepticism [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Burnstock's early hypothesis that ATP, the major intracellular molecule providing the energy required for multiple biochemical and biophysical processes, may actually function as an extracellular non-adrenergic and noncholinergic signaling molecule [12,13] was received with great skepticism [14,15]. After several decades of extensive work, the scientific community came to the realization that ATP is widely employed as a signaling molecule in multiple biological processes in both normal and pathophysiological conditions [9,11,[16][17][18][19][20][21][22][23][24]. The rapid progress in understanding and deciphering multiple molecular mechanisms of signaling revealed that ATP is a potent mediator of multiple signaling cascades, which may act through binding to, and nonhydrolytic activation of, P2X ionotropic receptors or G Electronic supplementary material The online version of this article (doi:10.1007/s11302-016-9520-9) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that A 3 activation via its selective agonist IB-MECA has previously been related to the stimulation of granulopoiesis, 24 , 25 and A 3 knockout mice display a reduction in mature granulocytes and monocytes compared to wild-type mice. 26 …”
Section: Discussionmentioning
confidence: 99%